Improving access of persons with hearing impairment to employment opportunities through collaboration of stakeholders in Oyo state, Nigeria (2018)
This study examined access to employment opportunities by individuals with hearing impairment through stakeholders’ collaboration. Descriptive survey research design was adopted to carry out the study. Purposive sampling technique was used to select 87 coworkers and government officials (stakeholders) in Oyo State, Nigeria. Three research questions were answered. A self designed questionnaire-Access to Employment by Persons with Hearing Impairment Questionnaire (AEPHIQ) (r=0.77) was used to collect data. The data collected were analysed, using descriptive statistics of frequency count and percentage. The study revealed that the level of awareness of stakeholders about disability and employment was very low, the attitude of stakeholders towards employees with hearing impairment was negative and there was no collaboration of stakeholders about the employment of employees with hearing impairment. There should be increased level of awareness of stakeholders about disability and employment, societal attitude towards employees with hearing impairment should be positive and there should be collaboration among stakeholders concerning the employment of employees with hearing impairment. These will improve access to employment of individuals with hearing impairment.